Women’s financial rights in light of the purposes of Islamic Sharia - Assaf, Mohammad Motlaq; Dibigh, Israa Mohammad (Journal of Islamic Sciences, 2022)
This research aimed to show the intentional aspect of women’s financial rights, clarify the loftiness of Islam in its view of women, and clarify the purposes of Islamic acceleration of women’s right to alimony due to kinship, and her right to inheritance, and the wife’s right to possess the dowry as well as her right to alimony due to marriage. In this study, it was based on the descriptive approach with the use of the deductive and analytical approaches, where the meanings of the most important terms related to the research were clarified, then the purposes of Sharia in the financial rights acquired by women, which are emanating from the marriage contract, were explained as the Sharia’s goal of the wife’s right to dowry and marital alimony. The study reached a set of results; the most important of which is that the purpose of Islamic legislation for alimony for a woman is to maintain her and preserve her dignity; thus, a man is adequate for her income-earning and guarantees her alimony. And as a guarantee for her if the husband abandons her, and that the inheritance system in Islam is not based on preference between men and women, but rather its wisdom is based on the standards of divine justice and the purposes of Islamic Sharia.